Finance basics : decode the jargon, navigate key statements, gauge performance - Harvard Business School (Boston, Massachusettes : Harvard Business Review Press, 2014)
Intimidated by corporate finance? The numbers (and the jargon) can feel overwhelming - but you have to understand them to manage effectively. Finance Basics explains the fundamentals simply and quickly, introducing you to key terms and concepts such as:How to navigate financial statements. How to weigh costs and benefits. What's involved in budgeting and forecasting. How to gauge a company's financial health
Tặng
Keywords: Corporations -- Finance; Managerial accounting